The judge in a democracy - Barak, Aharon (Princeton University Press, 2006)
Whether examining election outcomes, the legal status of terrorism suspects, or if (or how) people can be sentenced to death, a judge in a modern democracy assumes a role that raises some of the most contentious political issues of our day. But do judges even have a role beyond deciding the disputes before them under law? What are the criteria for judging the justices who write opinions for the United States Supreme Court or constitutional courts in other democracies? These are the questions that one of the world's foremost judges and legal theorists, Aharon Barak, poses in this book. In fluen.